2010
DOI: 10.1186/1742-4755-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Mothers, fathers, sons, and daughters: gender differences in factors associated with parent-child communication about sexual topics

Abstract: BackgroundIn the United States, nearly half of high school students are sexually active, and adolescents experience high rates of unintended pregnancy and sexually transmitted diseases. Parents can have an important influence on their children's sexual behaviour, but many parents do not talk with their children about sexual topics. Research has shown significant differences in parent-child communication about sexual topics depending on the gender of both the parent and the child. Little is known, however, abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 24 publications
5
52
0
1
Order By: Relevance
“…Parents demonstrated gender‐biased communication, in which they mainly spoke with their daughters about prohibitive sexual engagement. This finding supports previous reports in which female adolescents were the main focus of sexual communication in the USA (Wilson & Koo, ; Trinh et al ., ) and other Asian countries (Trinh et al , ; Zuo et al ., ). The gender‐biased parental communication in this study reinforces the traditional and stereotypical norms in sexual behavior, characterized by female premarital chastity and giving boys permission in Chinese society (Cui et al ., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Parents demonstrated gender‐biased communication, in which they mainly spoke with their daughters about prohibitive sexual engagement. This finding supports previous reports in which female adolescents were the main focus of sexual communication in the USA (Wilson & Koo, ; Trinh et al ., ) and other Asian countries (Trinh et al , ; Zuo et al ., ). The gender‐biased parental communication in this study reinforces the traditional and stereotypical norms in sexual behavior, characterized by female premarital chastity and giving boys permission in Chinese society (Cui et al ., ).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies focused on several specific topics, such as contraception, family planning, and abortion to explore participants' perspectives using qualitative approaches, mainly in Western countries (Akers et al , ; Sisco et al , ). Other studies applied surveys to describe factors associated with communication about specific sexual topics, such as abstinence, puberty, reproduction, birth, STI, dating and relationships (Wilson & Koo, ; Askelson et al , ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…55, 56 Yet many parents do not communicate with adolescents because of embarrassment, lack of confidence, and uncertainty about what to say. 57 Implementing a brief and effective intervention such as the FTT model is a way to improve parent–child communication and effectively monitor adolescent behavior, leading to delayed sexual debut and reduced frequency of sex. 58, 59 FTT provides guidance to nurses on topics to cover with parents to facilitate effective parent–child sexual health communication that takes the youth perspective into consideration.…”
Section: Calls For Improvementmentioning
confidence: 99%
“…Open communication at the family level can help to encourage adolescents to approach health care providers with questions and concerns related to their SRH [16] as well as encourage healthy sexual behaviour more generally [15,17,18]. Allen et al found that adolescent girls who communicate easily with their mothers were considerably less likely to become pregnant [19] and Wilson et al reported that open communication with parents led to postponed sexual debut and fewer unwanted pregnancies [20]. In semi-structured interviews conducted in the pre-intervention phase of Project CERCA, parents, young people, teachers and health providers in all three project sites acknowledged the difficulty and cultural taboos that prohibit the discussion of sex and sexuality within families, at school, and in the community as a whole.…”
Section: Methodsmentioning
confidence: 99%